2011
DOI: 10.1186/1471-230x-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and treatment outcomes of hepatoid adenocarcinoma of the stomach, a rare but unique subtype of gastric cancer

Abstract: BackgroundGastric hepatoid adenocarcinoma (HAC) is a special type of gastric cancer that morphologically mimics hepatocellular carcinoma. In this study, we performed an evaluation of clinicopathologic characteristics, treatment outcome, and prognosis in patients with gastric HAC.MethodsWe consecutively enrolled patients with pathologically proven gastric HAC at Seoul National University Hospital between January 1996 and December 2008 and conducted a retrospective review. Among 15,253 patients with gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 19 publications
(21 reference statements)
10
69
0
1
Order By: Relevance
“…[12,13] Our study revealed a similar incidence rate (0.22%) with a high incidence of metastasis. According to a previously published report, [14] patients with GHA have an average age of 63.5 years, are predominantly male (2.32:1), have tumors mainly located at the antrum, and tend to have high levels of AFP.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[12,13] Our study revealed a similar incidence rate (0.22%) with a high incidence of metastasis. According to a previously published report, [14] patients with GHA have an average age of 63.5 years, are predominantly male (2.32:1), have tumors mainly located at the antrum, and tend to have high levels of AFP.…”
Section: Discussionsupporting
confidence: 55%
“…As presented in our data, Borrmann's type III was the most common presentation of GHA, [13] which appeared as a fungating mass with a purple, berry-like surface [ Figure 2]. Ulceration in the presence of recent hemorrhage was also observed in some cases.…”
Section: Discussionmentioning
confidence: 74%
“…Survival is closely associated with the pTNM stage. Baek et al reported that the median overall survival of patients with stages I-III and stage IV was 28.0 and 8.2 months, respectively (9). Relatively longer survival requires accurate diagnosis at an earlier stage as well as active multimodality treatment, including radical gastrectomy and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in gastric tumor cases with an elevated serum AFP level, the possibility of HAS must be considered. Preoperative computed tomography and β-ultrasound of the liver are routinely recommended for the exclusion of HCC, hepatic metastasis, teratoma and other diseases that may also produce AFP (4,5,7). Histologically, the hepatoid structure identified in the gastric adenocarcinoma region may contribute significantly to the diagnosis (3)(4)(5)7).…”
Section: A B C Dmentioning
confidence: 99%
“…Preoperative computed tomography and β-ultrasound of the liver are routinely recommended for the exclusion of HCC, hepatic metastasis, teratoma and other diseases that may also produce AFP (4,5,7). Histologically, the hepatoid structure identified in the gastric adenocarcinoma region may contribute significantly to the diagnosis (3)(4)(5)7). Immunohistochemical analysis may exhibit positive staining for epithelial membrane antigen and CEA, which may aid in the exclusion of gastric metastasis of HCC (4,8,10,11).…”
Section: A B C Dmentioning
confidence: 99%